Two-dimensional ferromagnetic systems with finite driving. (May 2022) - Spasojević, Djordje; Janićević, Sanja
Abstract: We study the effect of finite driving by the time-varying external magnetic field in the two-dimensional disordered ferromagnetic systems portrayed on the case of nonequlibrium athermal random field Ising model. The response of studied systems is rate-dependent exhibiting scaling and data collapsing above the dynamical critical point in the full range of driving rates provided that the system parameters satisfy both the finite-size and here introduced rate-dependent scaling conditions. These findings are based on extensive numerical simulations of large systems reliably demonstrating the observed behavior and could be relevant for real thin systems driven at finite rates. Highlights: Response of disordered 2D ferromagnetic system depends on the rate of driving field. Proposed rate-dependent scaling allows data collapsing in the full range of rates. Three distinct domains of driving rate identified. At fast enough rates simultaneous avalanches merge dominating the dynamics. Results could be relevant for the real thin systems driven at finite rates.